ANALISIS RANTAI PASOK (Supply Chain) CABAI MERAH (Capsicum Annuum L.) DI STA MANTUNG KECAMATAN PUJON KABUPATEN MALANG. - Melia Agustin; Bambang Siswadi; Sri Hindarti (Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2019)
ABSTRACTThis study aims to determine supply chain management and marketing Sefficiency of red chili at STA Mantung. Data used are primary data from the results of observations and interviews conducted in December 2018 in STA Mantung, Pujon District, Malang Regency with determining the sample of farmers using the random sampling method and large traders using the snowball sampling method. amples used, namely 53 respondents: 30 farmers, 9 middlemen, 1 STA Mantung wholesaler, 9 retailers and 3 traders outside the STA Mantung.The results showed that the majority of farmers (82.5%) were directly sold to wholesalers at STA Mantung. There were four marketing channels at STA Mantung, namely: Channel I: Farmers, wholesalers, STA Mantung, End Customers. Channel II: Farmers - Middlemen - Wholesalers STA Mantung - Retailers = End Consumers. Channel III: Farmers - Large Traders of STA Mantung - Wholesalers Outside STA Mantung. Channel IV: Farmers - Large Traders of STA Mantung-Pabrik.Between the four channels the most efficient on the fourth channel. The market formed in STA Mantung is oligopoliKeywords: red chili, supply chain and marketing efficiency.